Inferring secondary cell wall-related R2R3-MYB transcription factor gene targets in Eucalyptus grandis using DNA affinity purification sequencing - Hussey, Steven G. (University of Pretoria, 2023)
Thesis (PhD (Genetics))--University of Pretoria, 2023.